Quality Assurance in Islamic Higher Education: Global Trends, Challenges, and Future Directions - Lia Yuliana; Syukrul Hamdi; Riki Perdana (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
This study conducts a systematic review of 32 articles on Quality Assurance (QA) in Islamic higher education, focusing on geographical contexts, methodological approaches, QA models used, QA dimensions studied, and supporting factors and challenges in QA implementation. The analysis reveals a dominance of research conducted in Indonesia (87%) with qualitative methods as the primary approach (75%), while quantitative and mixed-method studies remain limited. Popular QA models include Total Quality Management (TQM), the PDCA cycle, and the Internal Quality Assurance System (SPMI) with the PPEPP framework, supported by national and international accreditation such as BAN-PT, AUN-QA, and FIBAA. A key analytical finding of this review is that Islamic values are not merely presented as normative foundations but are operationalized within QA practices. Core values such as amanah (accountability), itqan (professional excellence), ihsan (continuous improvement), adl (fairness), and shura (participatory governance) are embedded in leadership decision-making, academic governance, curriculum quality control, and the development of internal quality culture. These values function as internal drivers that strengthen institutional commitment, ethical compliance, and sustainability of QA cycles. The most studied QA dimensions are institutional leadership, human resource development, teaching, and curriculum. Key findings indicate that systematic implementation of QA cycles and accreditation significantly improves accreditation status, institutional reputation, and graduate competitiveness. Main supporting factors include leadership commitment, internal QA regulations, HR training, and cross-institutional collaboration, whereas challenges include limited human resources, funding, organizational culture resistance, and readiness for international standards. The impact of QA is evident in improved academic quality, academic services, and research collaboration. This study recommends enhancing strategic leadership, strengthening HR capacity, digitalizing QA, and promoting global benchmarking as pivotal steps to sustain quality improvement in Islamic higher education towards achieving global reputation and international competitiveness.